Depressive Symptoms and 24-Hour Ambulatory Blood Pressure in Africans: The SABPA Study - Mark Hamer; Nancy Frasure-Smith; François Lespérance; Brian H. Harvey; Nico T. Malan; Leoné Malan (International Journal of Hypertension)
Disturbances in circadian rhythm might play a central role in the neurobiology of depression. We examined the association between depressive symptoms and 24-hour ambulatory BP in a sample of 405 (197 black and 208 Caucasian) urbanized African teachers aged 25 to 60 yrs (mean 44.6 ± 9.6 yrs). Depressive symptoms were assessed using the self-administered 9-item Patient Health Questionnaire (PHQ-9). After adjusting for age, sex, and ethnicity, participants with severe depressive symptoms (PHQ-9 ≥ 15) had higher odds of hypertension defined from ambulatory BP and/or use of antihypertensive medication (odds ratio = 2.19, 95% CI, 1.00–4.90) in comparison to participants with no symptoms. Compared to Caucasians with no depressive symptoms, those with severe symptoms had blunted nocturnal systolic BP drop of 4.7 mmHg (95% CI, −0.5 to 10.0, P=0.07). In summary, depressive symptoms were associated with the circadian BP profile in black and Caucasian Africans.